Information stream of demands of labour supply in the Lithuanian regional press - Stonkienė, Marija (Information & Media, 1997)
The author analyses the system of presenting information used in the Lithuanian Regional Press, according to the demands of the labour supply. The results of the survey make it possible to distinguish regions in Lithuania where the local labour market can be influenced by establishing and updating the system of providing information to the labour market.
Keywords: -